PERSPEKTIF GENERASI MILLENIAL TERHADAP EKSISTENSI BAHASA INDONESIA DI MEDIA SOSIAL - Aulia, Ayu Nisrina; Nuriyam, Sajdah; Mahardika, Reka Yuda (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Language is man’s means for thinking what were the earliest sources of man’s gaining insight and science. Regarding the existence of the Indonesian language, researchers here gather data, record interviews and analyze each of respondents answer. This study was intended to try to understand how individuals are concerned about Indonesian language positions. The reason researchers took this heading is because today the Indonesian function feels like it’s beginning to shift with the foreign language and because it’s an attitude that believes that it tooks more modern if it’s in foreign language interacting on social media. This study is important and beneficial to readers because of the problems they describe, there is no other way but to reaffirm the importance of good and proper observance of Indonesian language. The research method used is a qualitative research method also referred to as an investigative approach because it’s common for researchers to collect data by face-to-face contact with people in the research facility. The result of this study is that the Indonesian language has not been used properly. Many of speakers are still plagued by low self-esteem, it makes feel more honorable, better educated if in the events of daily speech, both in oral and writing variety, slipped a stack of foreign terms, even though there is an equivalent in Indonesian.